Multiplex PCR for the Identification of Pathogenic Listeria in Flammulina velutipes Plant Based on Novel Specific Targets Revealed by Pan-Genome Analysis - Li, Fan; Ye, Qinghua; Chen, Moutong; Zhang, Jumei; Xue, Liang; Wang, Juan; Wu, Shi; Zeng, Haiyan; Gu, Qihui; Zhang, Youxiong; Wei, Xianhu; Ding, Yu; et al. (Frontiers in Microbiology, 2021)
Listeria spp. is an important foodborne disease agent, often found in the fresh mushroom (Flammulina velutipes) and its production environment. The aim of this study was to develop multiplex PCR for rapid identification of Listeria monocytogenes and Listeria ivanovii, and nonpathogenic Listeria in F. velutipes plants. Pan-genome analysis was first used to identify five novel Listeria-specific targets: one for the Listeria genus, one for L. monocytogenes, and three for L. ivanovii. Primers for the novel targets were highly specific in individual reactions. The detection limits were 103–104 CFU/mL, meeting the requirements of molecular detection. A mPCR assay for the identification of pathogenic Listeria, with primers targeting the novel genes specific for Listeria genus (LMOSLCC2755_0944), L. monocytogenes (LMOSLCC2755_0090), and L. ivanovii (queT_1) was then designed. The assay specificity was robustly verified by analyzing nonpathogenic Listeria and non-Listeria spp. strains. The determined detection limits were 2.0  103 CFU/mL for L. monocytogenes and 3.4  103 CFU/mL for L. ivanovii, for pure culture analysis. Further, the assay detected 7.6  104 to 7.6  100 CFU/10 g of pathogenic Listeria spiked into F. velutipes samples following 4–12 h enrichment. The assay feasibility was evaluated by comparing with a traditional culture-based method, by analyzing 129 samples collected from different F. velutipes plants. The prevalence of Listeria spp. and L. monocytogenes was 58.1% and 41.1%, respectively. The calculated κ factors for Listeria spp., L. monocytogenes, and L. ivanovii were 0.97, 0.97, and 1, respectively. The results of the novel mPCR assay were highly consistent with those of the culture-based method. The new assay thus will allow rapid, specific, and accurate detection and monitoring of pathogenic Listeria in food and its production environment.